History in Practice: An Interview with Dr Frances Flanagan - Limina Collective (Limina: A Journal of Historical and Cultural Studies, 2011)
Frances Flanagan is an Arts/Law graduate from the University of Western Australia. She has a DPhil in modern Irish history from Oxford University. Her thesis, entitled 'Your Dream Not Mine: Nationalist Disillusionment and the Memory of Revolution in the Irish Free State' is soon to be published by Oxford University Press.